2001
DOI: 10.1364/ao.40.001735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of refractive index on the measurement of optical properties in turbid media

Abstract: Continuous-wave measurement-based methods offer a rapid cost-effective way to determine optical properties in turbid media. This method requires a measure of the refractive index of the medium, which is often unknown a priori. Whereas previous studies have reported that the refractive index has little impact on the measurement of optical properties, here we show a significant effect of refractive indices on measurements, using both simulations and experiments. In addition we propose a noniterative method to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…When absorption by the material is small, most of the energy flux is carried by the diffuse component. The effective RI assigned to the coherent component of light has been investigated in recent years [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and its nonlocal nature has been established [19,25]. However, as already said the effective RI seen by diffuse light has been barely investigated, and the only reference reporting efforts in the past that helps address this question is that of Meeten and North [6].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…When absorption by the material is small, most of the energy flux is carried by the diffuse component. The effective RI assigned to the coherent component of light has been investigated in recent years [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and its nonlocal nature has been established [19,25]. However, as already said the effective RI seen by diffuse light has been barely investigated, and the only reference reporting efforts in the past that helps address this question is that of Meeten and North [6].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…1 Limited studies have shown that refractive index can be used in modeling of tissue optics to characterize the effect of sample interfaces with ambient media on the inverse determination of bulk parameters and light distribution in heterogeneous tissues. [2][3][4] It is therefore an important task to obtain accurately the refractive index of tissues and its variation with wavelength for further improving tissue optics modeling, image reconstruction, 5 and instrumentation development.…”
Section: Introductionmentioning
confidence: 99%
“…As observed by Bartlett and Jiang [21], the chosen n value may influence μ a and μs estimation. This observation was obtained for a semi-infinite medium, a geometry different from the used cubic OP sample.…”
Section: Discussionmentioning
confidence: 99%